Процес та наслідки націоналізації “приватбанку” - Горбаль, Н. І.; Гошовська, О. В.; Полтавцева, А. І.; Horbal, N. I.; Hoshovska, O. V.; Poltavtseva, A. I. (Видавництво Львівської політехніки, 2017)
Розглянуто сутність та значення націоналізації банків, проаналізовано її особливості у світі та в Україні. Висвітлено основні показники діяльності ПриватБанку, визначено основні проблеми і вимоги до банку на момент націоналізації. Визначено основні наслідки переходу ПриватБанку у власність держави, розглянуто основні причини негативного впливу націоналізації банку на ситуацію в державі.

The essence and significance of nationalization were reviewed, historical information about the global banks’ nationalization was represented, also the current state of the Ukrainian banking system was analyzed. Moreover, the basic indicators of PrivatBank, the main problems and requirements to the bank were shown. The article aims to research the pre-conditions, expediency and consequences of nationalization of PrivatBank, determining the prospects of its development. As of today there are a few methods of restoring the financially helpless banks, id est proceeding in their functioning. The main of them include refunding, temporarily administration of a bank and nationalization. Nationalization is the process of transforming private assets into public ones by bringing them under the public ownership of a national government or state. The current financial crisis has put a strict requirement of additional capitalization for the Ukrainian banks as the only possibility for their further existence. In other case they can face strengthening of problem of insolvency and even exit a market. In Ukraine the problems in banking sector have been observed already for a few years, in particular from the moment of political changes and beginning of military conflict at the East of Ukraine (yrs 2013-2014). These events take place next to worsening of situation at the basic industrial markets, low business activity in the banking system and unstable and expensive resource base (money attracted by banks). As the result the banks do not meet the obligations and begin to work unstably. The basic indications of the situation are limitations on activity with cards, accounts and deposits. The banks clients, both private and legal entities, try to leave the banks and withdraw the valuable cash resources from the banks, which results in limited working capital. First of all, the National bank of Ukraine begins to give to such banks money for refunding, that for essences must even balance of receivables, charges and obligations, but it is only a temporal effect PrivatBank is the biggest bank in the country as for the value of assets and the number of clients. In general there were two key requirements in relation to the bank activity at the end of 2016, including: 1. Enormous debt against the National bank. Alhrough there are huge amounts of refunding and stabilization loans from the National Bank of Ukraine to PrivatBank has a number of limitations with respect to the influence on the bank activity; 2. Considerable volume of loans to the “constrained persons” – companies that are related to the proprietors of bank. Also, the basic effects of PrivatBank transition to the state was analysed, considered the main reasons of bad influence of bank nationalization on the country’s life. Considering that PrivatBank is a system-supporting entity, the procedure of its liquidation is impossible, as it would cause too significant and negative social effect. PrivatBank served 20 million clients. If it “fell” down, all banking system of Ukraine would “fall” down as well. Nationalization of such a large Ukrainian bank will substantially influence the financial state of the country for the following reasons: it will loosen the holds of the state on functioning of the system; corruption risks will increase; unsecured loans will hardly be repaid. On the whole for the last three years the banking sector has undergone unprecedented cleanup (from the beginning of 2014 till beginning of 2017 87 banks have disappeared from the market). For realization of payments according to obligations against the private clients deposit insurance fund is forced to take new borrowings from the state, which influences the level of national debt. The prospects of money repayment, that were on the accounts of enterprises in banks, in relation to that made decision about introduction of temporal administration or liquidations, is practically absent, as an evaluation cost of assets of such banks in several times less than their book value. Because of leadingout of banks from a market considerable losses were got by legal entities and private persons, as a result the financial state of many enterprises became substantially worse, some of them going bankrupt, and the state received less tax receivabless. Nationalization of one of the biggest banks in the country (PrivatBank) was one of the forced steps of such process of cleanup. Reactivation of normal work of the bank, as well as reconstruction of functioning of the banking system on the whole, will require quite a bit of time.
The process and consequences of privatbank nationalization
Keywords: банк; банківська система; націоналізація; рефінансування; активи; кредитний ризик; держава; борг; bank; the banking system; nationalization; refinancing; credit risk; assets; state; debt; 336; 338